Rancang Bangun Sistem Kendali Motor Stepper Printer Canon BJC-S200SPx untuk Prototipe Lengan Robot 5-DOF (Majabot) - Saputra, Hendri Maja (INKOM Journal, 2010)
Designing and building of motor stepper control system from unused printer Canon BJC-S200SPx of robot arm prototype with five degree of freedom (5-DOF) has been developed. That printer type is used because if trouble occur it is not only very difficult but also expensive to be repaired, so it is sold very cheap or misspent. Robot arm has 5 revolution joints, wherein each joint is limited by one degree of freedom to make the manipulator control systems and mechanics work easier. To control the systems device, it needs driver (control circuit) with data input in the form of computer command using programming software, with parallel port communicated in order to generate motor stepper pulses. The experiment results showed that low-precisian of robot arm movement occur cumulatively, although hardware and software control systems had been designed optimally.